Artemisinins in Combating Viral Infections Like SARS-CoV-2, Inflammation and Cancers and Options to Meet Increased Global Demand - Farmanpour-Kalalagh, Karim; Beyraghdar Kashkooli, Arman; Babaei, Alireza; Rezaei, Ali; van der Krol, Alexander R. (Frontiers in Plant Science, 2022)
Artemisinin is a natural bioactive sesquiterpene lactone containing an unusual endoperoxide 1, 2, 4-trioxane ring. It is derived from the herbal medicinal plant Artemisia annua and is best known for its use in treatment of malaria. However, recent studies also indicate the potential for artemisinin and related compounds, commonly referred to as artemisinins, in combating viral infections, inflammation and certain cancers. Moreover, the different potential modes of action of artemisinins make these compounds also potentially relevant to the challenges the world faces in the COVID-19 pandemic. Initial studies indicate positive effects of artemisinin or Artemisia spp. extracts to combat SARS-CoV-2 infection or COVID-19 related symptoms and WHO-supervised clinical studies on the potential of artemisinins to combat COVID-19 are now in progress. However, implementing multiple potential new uses of artemisinins will require effective solutions to boost production, either by enhancing synthesis in A. annua itself or through biotechnological engineering in alternative biosynthesis platforms. Because of this renewed interest in artemisinin and its derivatives, here we review its modes of action, its potential application in different diseases including COVID-19, its biosynthesis and future options to boost production.